Anal fistula associated mucinous adenocarcinoma with anal fissure: a case report - Tompe, Nikita; Rizvi, Shaheen; Sawant, Sharadkumar Pralhad (International Journal of Research in Medical Sciences, 2024)
Perianal abscesses and anal fistulas are interconnected phases of an infectious process. Persistent irritation and inflammation around an anal fistula can cause cellular changes that increase the risk of cancerous transformation. A long-standing anal fistula, persisting for over 10 years, has been recognized as a potential precursor to fistula-associated mucinous adenocarcinoma (FAMC). A 67-year-old male patient presented with complaints of intense anal pain and a palpable tumor last year. Examination revealed a gluteal abscess, fistula-in-ano and an anal fissure. The patient gave a history of perianal abscess and anal fistula treated three years ago with fistulectomy, pus drainage, and lateral anal sphincterotomy. MRI revealed a horseshoe-shaped, multiseptate abscess in the intersphincteric plane (1 to 9 o’clock, predominantly left-sided), displacing the anal canal to the right, with three intersphincteric fistulas connected to the tumor. Histopathological examination revealed well to moderately differentiated mucinous adenocarcinoma in the distal aspect of the fistula suggesting a direct link between the chronic inflammatory process and development of malignancy. FAMC is a rare but serious complication of chronic anal fistulas. The diagnosis was made three years after treating a perianal abscess, indicating that epithelial dysplasia and carcinogenesis may have begun before the abscess developed. Consequently, FAMC can arise from anal fistulas in fewer than 10 years. This case underscores the importance of careful monitoring of patients with a history of perianal abscesses or anal fistulas for signs of malignant transformation, as early detection can significantly impact prognosis and treatment outcomes.